Studi awal uji aktivitas enzim amilase dari tumbuhan secara kualitatif berdasarkan perbedaan suhu dan konsentrasi substrat - Muliasari, Handa; Permatasari, Lina (Journal of Agritechnology and Food Processing, 2022)
Amylase enzyme is a starch hydrolyzing enzyme that has wide applications in the food, beverage and biotechnology industries. One source of the amylase enzyme that is easily obtained is plant seeds and sprouts. This research is a preliminary study to qualitatively test the activity of the crude extract of the amylase enzyme from plants. Amylase enzyme was obtained from green bean sprouts, fresh and dried peanut seeds, and fresh and dried corn seeds. The crude extract of the amylase enzyme was tested for its activity using 1% starch as a substrate with variations in temperature and amount of substrate. The result of starch hydrolysis in the form of reducing sugar was detected using Benedict's reagent. The experimental results showed that the amylase enzyme extracted from green bean sprouts and fresh and dried corn kernels showed activity in breaking down starch at 25oC using 6 mL substrate concentration, while dried peanut seeds showed no activity. The enzyme activity is influenced by temperature and the amount of substrate.